THE EFFECT OF MARKET ORIENTATION, PRODUCT INNOVATION AND CREATIVITY OF BUSINESS ACTOR ON MARKETING PERFORMANCE IN MSMES (STUDY ON COFFEE MSMES IN NORTH ACEH REGENCY) - Muchsin, Muchsin; Rahmaniar, Rahmaniar; Subhan, M. (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Marketing is how to meet or satisfy the needs of consumers through certain distribution channels through the products offered. The number of coffee shops located in various places is unique for the people of Aceh which creates high competitiveness among coffee shop owners, so an optimal strategy is needed to be able to compete with other coffee shop owners. In order to compete, it is necessary to develop strategies and innovations, this is necessary because a good innovation will get a response from consumers. Innovation is important to maintain competitive advantage. This study aims to determine the development of coffee shops in North Aceh district and to determine the performance of the influence of market orientation, product innovation and creativity of business actors on marketing performance of coffee SMEs in North Aceh district. The variables used in this study are market orientation, product innovation, and creativity of business actors as independent variables, and marketing performance as the dependent variable. Research Analysis This research uses quantitative research. The data sources in this study are primary data where the method of collecting data and conducting direct observations to observe the behavior and activities of Aceh coffee shops and the questionnaire method distributed to coffee SMEs in North Aceh district. The results of this study indicate that market orientation has a positive and significant effect on marketing performance. Product innovation has a positive and significant effect on marketing performance. The creativity of business actors has a positive and significant effect on marketing performance. Market orientation, product innovation, and creativity of business actors have a simultaneous (simultaneous) effect on marketing performance. The outputs in this study consist of publications in national journals and IPR.